(untitled) (Journal of the College of Basic Education, 2022)
The study of population is one of the important studies on which all activities, whether natural or human, are based, so the aim of the research is to study the demographic gift in Iraq through quantitative analysis and interpretation of the age structure and population growth and what are the most important reflections on the current economic situation of the country, that the changes occurring in The age structure is characterized by an increase in the size of the population of working and productive age in exchange for a decrease in the dependent age groups (young and old). This change can produce a window of opportunity for development through the development, building and development of human capabilities depending on the interconnectedness and interaction between the efficiency and skill of human resources at the level of education. And what the development process requires, and through these demographic changes and the extent to which they take, it is necessary to approach the extent of the openness of the demographic window and its availability through full development opportunities and between the determinants and restrictions at the local and national levels represented in building levels of human capital and enhancing the skill that provides suitable job opportunities. As well as the optimal investment of available resources, in light of sustainable human development standard .